2014
DOI: 10.1590/s2175-62362014000200010
|View full text |Cite
|
Sign up to set email alerts
|

Sujeitos, políticas e educação ambiental na gestão de resíduos sólidos

Abstract: RESUMO -Sujeitos, Políticas e Educação Ambiental na Gestão de ResíduosSólidos. As análises que apresentamos aqui se configuram na articulação com os debates sobre a sustentabilidade do modelo de produção e consumo que temos gerado, problematizando políticas e práticas educativas gestadas na constituição e funcionamento das atividades de coleta seletiva e reciclagem. Procuramos, neste ínterim, abordar relações, tomadas de posição e contradições que constituem os aparatos públicos de reciclagem, considerando as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
1
0
3
Order By: Relevance
“…The Brazilian government has not regulated the relations between these actors and there are no fiscal or financial incentives for recycling yet. Some studies have found that the recycling trade can be unfair for pickers, autonomous and within co-operatives, who are the most vulnerable actors in the chain (AVINA, 2008;Furlan, 2007;Pinheiro et al, 2014). That is why co-operatives are starting to unite in regional networks, taking up the role of accumulating materials to sell directly to the recycling industry, bypassing intermediate actors (Pinheiro et al, 2014;Rutkowski and Rutkowski, 2015).…”
Section: History Of Irs Integrationmentioning
confidence: 99%
“…The Brazilian government has not regulated the relations between these actors and there are no fiscal or financial incentives for recycling yet. Some studies have found that the recycling trade can be unfair for pickers, autonomous and within co-operatives, who are the most vulnerable actors in the chain (AVINA, 2008;Furlan, 2007;Pinheiro et al, 2014). That is why co-operatives are starting to unite in regional networks, taking up the role of accumulating materials to sell directly to the recycling industry, bypassing intermediate actors (Pinheiro et al, 2014;Rutkowski and Rutkowski, 2015).…”
Section: History Of Irs Integrationmentioning
confidence: 99%
“…Nesse contexto, tornou-se perceptível a importância e valorização da prática das estratégias em Educação Ambiental na construção e manutenção de um meio ambiente ecologicamente equilibrado, onde a população tenha consciência para enxergar sua responsabilidade diante o atual cenário brasileiro e, com isso, participe de processos Estudos em Direito Ambiental: Desenvolvimento, desastres e regulação | 281 decisórios que visem à sustentabilidade socioambiental e projetos socioeducativos em parceria com a Gestão Pública (Pinheiro, et al, 2014).…”
Section: Definição De Procedimentos Para Coleta De Dadosunclassified
“…Nesse contexto, tornou-se perceptível a importância e valorização da prática das estratégias em Educação Ambiental na construção e manutenção de um meio ambiente ecologicamente equilibrado, onde a população tenha consciência para enxergar sua responsabilidade diante o atual cenário brasileiro e, com isso, participe de processos Estudos em Direito Ambiental: Desenvolvimento, desastres e regulação | 281 decisórios que visem à sustentabilidade socioambiental e projetos socioeducativos em parceria com a Gestão Pública (Pinheiro, et al, 2014).…”
Section: Introductionunclassified